Glikogen Otot Rangka Ayam Broiler (Gallus gallus) setelah Pemberian Teh Kombucha dalam Air Minum - Fathoni, Nasrul; Djaelani, M Anwar; Isdadiyanto, Sri (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
Kombucha tea beverage obtained by fermenting sweetened green tea for 12 days with Acetobacter xylinum and Saccharomyces which produce various kinds of organic acids, vitamins, and acts as a probiotic. The role of kombucha tea as a growth promoter is to that improve the metabolic process in the digestion of broiler chickens, so that nutrients can and fulfilled optimally for growth and development. The aim of this research was to analyze the sceletal muscle glycogen glycogen (Gallus gallus) after treat with kombucha tea in drinking water. Kombucha tea used is the result of fermentation of green tea for 12 days. This research used DOC chickens (Day Old Chicken) as much as 20 randomly divided into 4 treatments with concentration ie 0%, 10%, 20%, and 40% kombucha tea in drinking water for 32 days. The variables measured were skeletal muscle glycogen levels, body weight, feed consumption and drink consumption. The data obtained were analyzed using ANOVA followed by Duncan Test with 95% confidence level using SPSS 17.0 software. The results of this study showed that kombucha tea on skeletal muscle glycogen and feed consumption showed no significant difference, while on body weight and drink consumption showed significantly different results. Based on the results of the study, it can be concluded that giving kombucha tea in drinking water to a concentration of 40% has not been able to affect the skeletal muscle glycogen in broiler chickens.Â Key words: Kombucha tea, broiler chicken, glycogen skeletal muscle